2014
DOI: 10.1002/2013jd020424
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐FOV Raman and Doppler lidar studies of aerosol‐cloud interactions: Simultaneous profiling of aerosols, warm‐cloud properties, and vertical wind

Abstract: For the first time, colocated dual‐field of view (dual‐FOV) Raman lidar and Doppler lidar observations (case studies) of aerosol and cloud optical and microphysical properties below and within thin layered liquid water clouds are presented together with an updraft and downdraft characterization at cloud base. The goal of this work is to investigate the relationship between aerosol load close to cloud base and cloud characteristics of warm (purely liquid) clouds and the study of the influence of vertical motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 77 publications
2
51
0
Order By: Relevance
“…The estimated n CCN values are no longer trustworthy for higher relative humidities, i.e., for example in the subcloud layer (from 500 m below cloud base to cloud base), i.e., in the humid layer right below the base of a convective cloud system (Schmidt et al, 2014). It remains to be investigated to what extent our method can be used for relative humidities > 80 % and also for humidities < 40 %.…”
Section: Continental Marine and Desert Aerosol Conversion Parametermentioning
confidence: 98%
See 1 more Smart Citation
“…The estimated n CCN values are no longer trustworthy for higher relative humidities, i.e., for example in the subcloud layer (from 500 m below cloud base to cloud base), i.e., in the humid layer right below the base of a convective cloud system (Schmidt et al, 2014). It remains to be investigated to what extent our method can be used for relative humidities > 80 % and also for humidities < 40 %.…”
Section: Continental Marine and Desert Aerosol Conversion Parametermentioning
confidence: 98%
“…logical conditions with high vertical and temporal resolution (Illingworth et al, 2007;Shupe, 2007;Ansmann et al, 2009;de Boer et al, 2011;Schmidt et al, 2014).…”
Section: R E Mamouri and A Ansmann: Lidar Profiling Of Ccn-and Inpmentioning
confidence: 99%
“…Both approaches are based on the relationship between r e and the intensity of forward scattering. Based on a forward iterative algorithm that uses the measured signals from a Raman lidar at two fields of view Schmidt et al (), Schmidt et al () demonstrated the derivation of profiles of the r e , extinction coefficient, L , and N d of liquid water clouds. The uniqueness of this dual‐field‐of‐view method is that light is detected which was scattered in the forward direction by cloud droplets but backscattered inelastically by nitrogen molecules.…”
Section: Ground‐based Remote Sensing Approachesmentioning
confidence: 99%
“…Ground-based active remote sensing is, in general, of great importance for observational studies of aerosol-cloud interactions because of its unique potential to observe aerosol layers and clouds (from base to top) with high vertical and temporal resolution and this over long time periods (Ansmann et al, 2005(Ansmann et al, , 2009Illingworth et al, 2007;Martucci and O'Dowd, 2011;de Boer et al, 2011;Kanitz et al, 2011;Wandinger et al, 2012;Bühl et al, 2013;Schmidt et al, 2014). Continuously running stations can provide dense aerosol-cloud data sets for statistical analysis for all seasons of the year.…”
Section: Introductionmentioning
confidence: 99%